Är renar och kolt allt? : En studie om hur fem samer upplevde att de representeras i media och hur Dagens Nyheter beskrev samer under 2018 - Alexandersson, Emma (Karlstads universitet, Institutionen för geografi, medier och kommunikation (from 2013), 2020)
The purpose of this thesis is to compare five interviewees personal and collective experience of representations in media to articles published in the Swedish daily newspaper Dagens Nyheter containing the words related to the Sami population (namely: same, samer, samisk and samiska). Four research questions and their underlying factors are central to the study. The first two concern the interviews: How do the interviewees perceive representations of the Samis in media and the majority society? Do the interviewees feel personally represented by that? Answers to those questions are converted into themes that form the basis of a thematic text analysis of the articles which in turn respond to the other two research queries: Are the images painted by the interviewees present in the articles published by DN under 2018? Are there patterns in how DN writes about the Samis? The interviewees testified to a largely coherent picture of a Sami. Its basis is reindeer herding, traditional clothing (kolt) and an interest in nature. Another picture for which they find news media being responsible for is the ‘discontent Sami’. The imagery is narrow and hard for Samis outside of reindeer husbandry to identify with. The same imagery was present in DN, and were both confirmed and contrasted. To the extent to which generalised patterns could be found, there was a tendency to chooses the side of the Sami community and to justify collective Sami discontent through giving a historic background to conflicts. Uppsatsens syfte är att jämföra fem intervjupersoners upplevelse av hur samer representeras i media med artiklar publicerade i Dagens Nyheter innehållandes något utav sökorden same, samer, samisk och samiska. Fyra forskningsfrågor och dess bakomliggande faktorer driver studien. De två första frågorna vänder sig till intervjumaterialet: Hur upplever intervjupersonerna att samer representeras i media och storsamhället? Känner intervjupersonerna att den generella bilden representerar hen personligen? Svaren där ligger sedan till grund ...